Who bears labour taxes and social contributions? A meta-analysis approach - Ángel Melguizo; José Manuel González-Páramo (SERIEs - Journal of the Spanish Economic Association, 2013)
In this paper we apply the meta-regression technique to survey the empirical literature on the economic incidence of labour taxes and social security contributions. In particular, we focus on the effects of taxation on wages to test the conventional view that employees bear the burden due to lower net wages. Based on 52 empirical papers, we find that economic institutions, the tax wedge definition, and the temporal focus significantly affect the results. In the long run, workers bear between two thirds of the tax burden in Continental and Anglo-Saxon economies, and nearly 90 % in the Nordic economies. However, despite the numerous set of controlling variables, a significant part of the variability of the empirical literature remains unexplained.
Keywords: C83; E24; H22; 330; labour taxes; incidence; meta-analysis; Einkommensteuer; Steuerinzidenz; Sozialversicherungsbeitrag; Steuerbelastung; Meta-Analyse; Welt